2005
DOI: 10.2134/jeq2005.0350
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Runoff and Associated Nitrogen Losses from Turfgrass using the Root Zone Water Quality Model (RZWQM)

Abstract: Nitrogen fertilizers are used to maintain optimum turfgrass quality, but off-site movement of this primary nutrient can affect water quality. We conducted a 4-yr study (1998-2001) designed to measure nitrate N runoff from turfgrass, gathering data to be used in the model. The process-based Root Zone Water Quality Model (RZWQM) was used to predict nitrate associated with runoff from turfgrass. The measurements were made on 12 sloped (5%), 25-m2 plots of 'Tifway' bermudagrass [Cynodon dactylon (L.) Pers.], manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The greater runoff coefficients were generally associated with more intense high volume rainfall events. The monthly runoff coefficients measured in this study were in the range with those reported from other turf studies (Smith and Bridges, 1996;Linde and Watschke, 1997;Shuman, 2002;Easton and Petrovic, 2005;Schwartz and Shuman, 2005).…”
Section: Results and Discussion Hydrologysupporting
confidence: 87%
“…The greater runoff coefficients were generally associated with more intense high volume rainfall events. The monthly runoff coefficients measured in this study were in the range with those reported from other turf studies (Smith and Bridges, 1996;Linde and Watschke, 1997;Shuman, 2002;Easton and Petrovic, 2005;Schwartz and Shuman, 2005).…”
Section: Results and Discussion Hydrologysupporting
confidence: 87%
“…For the most part, chemical transport modeling of turf has been performed using existing agricultural or watershed models such as GLEAMS (Smith and Tillotson, 1993; Ma et al, 1999a), EPIC (King and Balogh, 1997; King and Balogh, 1999), PRZM (Cohen et al, 1993; Ma et al, 1999a; Durborow et al, 2000), SWAT (King and Balogh, 2001), Opus (Ma et al, 1999b), EXPRES (Roy et al, 2001), and RZWQM (Schwartz and Shuman 2005). To our knowledge the only model developed specifically for turf grass is TurfPQ (Haith, 2001; Haith, 2002).…”
Section: Pesticide Application Rate and Select Propertiesmentioning
confidence: 99%
“…However, changes in rainfall intensity, timing, and/or duration can alter nutrient and sediment loading. Schwartz and Shuman (2005) reported nutrient losses to be greatest for the first runoff event after application, especially as rainfall intensity and duration increased. In the current experiments, P was not applied in initial or subsequent fertilizations; however increasing bermudagrass groundcover through higher planting rates filtered more sediment and thus has a greater potential to reduce offsite soil‐bound P transport.…”
Section: Discussionmentioning
confidence: 99%